Relationships Between Cell Structure Alterations and Berry Abscission in Table Grapes - Li, Mingjuan; Huang, Zhanwen; You, Xiangrong; Zhang, Yayuan; Wei, Ping; Zhou, Kui; Wang, Ying (Frontiers in Nutrition, 2020)
The aim of this study was to explore the relationships between cell structure alterations and postharvest berry abscission in ‘Muscat Kyoho’, ‘Kyoho’ and ‘Nanyu’ table grapes stored for 0 d, 3 d or 6 d at room temperature. Microstructure analysis showed that a large number of the stalk-berry junction cells of ‘Muscat Kyoho’ and ‘Kyoho’ were lignified and suberized at 0 d, whereas these events seldom occurred in ‘Nanyu’. Furthermore, the berry brush cells of the three varieties, especially those of ‘Nanyu’, were small and dense. At 3 d, the numbers of lignified and suberized cells of ‘Muscat Kyoho’ and ‘Kyoho’ were reduced, and the cells had degraded, ruptured and disappeared by 6 d. The berry brush cells of ‘Muscat Kyoho’ and ‘Kyoho’ were larger and more loosely arranged than were those of ‘Nanyu’. Ultrastructure analysis showed that the cells increased in size from small to large and became loosely arranged; the smallest changes were observed in ‘Nanyu’. The cells of ‘Muscat Kyoho’ and ‘Kyoho’ were hydrolyzed, liquated and covered by granular substances at 6 d, and these features were especially prominent in ‘Muscat Kyoho’. The detachment force of grapes declined steadily (p<0.05) and was accompanied by an increase in berry abscission. ‘Nanyu’ maintained the highest detachment force and the lowest berry abscission during storage (p<0.05), followed by ‘Kyoho’ and ‘Muscat Kyoho’. The structural alterations were directly related to berry abscission and correlated inversely with detachment force, with the greatest alterations occurring in ‘Muscat Kyoho’, followed by ‘Kyoho’ and then ‘Nanyu’.